Folk consciousness sleep: features of functioning (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is devoted to the study of structural features of folk dream interpretation (sleep and dreaming) from the point of view of the manifestations of national mentality and reflect fragments of the national character of the Ukrainian people. In the article the analysis of dreams based on the folk classification of sleep suggested by Nicholas Dmytrenko.
Keywords: sleep; dream; classification; vision; the people; the mentality